Die Kopenhagener Ørestad und die Hamburger Hafencity - Chancen und Risiken marktorientierter Ansätze bei städtebaulichen Großvorhaben - Priebs, Axel (ERDKUNDE, 2000)
To develop large scale projects of strategic importance many cities increasingly use market economy instruments. They do not only act as public bodies but also use the opportunities to operate on the property market with their own development corporations. With Ørestad in Copenhagen and HafenCity in Hamburg as examples the application of market economy instruments is discussed in these projects. It is obvious, that a sophisticated use of those instruments on the one hand extends the cities’ freedom of action. On the other hand, this may involve a certain risk that economic considerations might compete with the interests of public welfare.